Analisis Pedagang Kaki Lima Di Obyek Wisata Grojogan Sewu Kecamatan Tawangmangu Kabupaten Karanganyar 2009 - 2013 - Prasepta, Wahyu Eka; , Dra. Hj. Umrotun, M.Si; , Dra. Hj. Retno Woro Kaeksi (2015)
Grojogan Sewu is the most crowded tourist attraction than other tourist attraction that located in the District of Tawangmangu, Karanganyar. To obtain maximum results in Grojogan Sewu tourism should, as well as the arrangement of street vendors (PKL) is done, in order that the visitors feel comfort and the street vendor get income maximum from the trading transactions in Grojogan Sewu. Related to this case, the objectives of this research are: (1) Determining the distribution of street vendors' origin in Grojogan Sewu Tourism. (2) Determining the factors that attract people to trade in Grojokan Sewu Tourism. (3) Analyzing the factors that affect the income level of street vendors in Grojogan Sewu Tourism. The results of this research showed (1) more than 80% of street vendor comes from the local of Karanganyar or areas close the Grojogan Sewu Tourism. (2) The factors that affecting street vendors to trade are market size and strategic location that promises many advantages for them, because Grojogan Sewu is the place that most like to visit in Tawangmangu. The analysis shows that visitors are included in the highest respondents is frequency 109 people in the presentage is 58,28%, whereas for the factors category that make people interested the lowest respondents is the frequency of 78 people in precentage 41.71%. (3) There are many things that influence the level of income received by street vendors; they are the location, the old business, the products sold and the services provided. The calculation result of income for category factors that affect the income level of the people to the highest responder types of non-food commodities which have an average income is Rp. 4.607.575/month and factors that affect the lowest income levels in the form of food to an average is Rp. 3.009.917/month